2022
DOI: 10.56059/jl4d.v9i2.617
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Evaluating the Use of Distance Learning Systems in the Context of the Unified Theory of Acceptance and Use of Technology-2

Abstract: Various theories and models are used to understand the impact of technology in education. One of these models is the UTAUT-2 model. This model allows us to understand the acceptance and use of technology. In this study, students' intentions and behaviours related to using the UBYS system, which is used as a learning management system, were examined within the framework of the UTAUT-2 model. The structural equation model was also used in the study. Smart PLS 3.3.5 and IBM SPSS Statistics v20.0 programmes were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In information system research, HM has been found to influence technology acceptance and use (Childers et al, 2001;Thong et al, 2006;Van der Heijden, 2004). From the literature, HM is generally a predictor of BI, a finding that is aligned with what was proposed by Venkatesh et al ( 2012) (Ashraf et al, 2023;Avci & Acvi, 2022, Azizi et al, 2020Bervell et al, 2021;de Moraes & Cabello, 2017;Fathima Sanjeetha & Sabraz Nawaz, 2020;Hu et al, 2020, Kalinkara & Talan, 2022Kumar & Bervell, 2019;Moorthy et al, 2019b;Nikolopoulou et al, 2020;Raman & Don, 2013;Zhou et al, 2022). However, when Tamilmani et al (2019) conducted a meta-analysis of 79 UTAUT2 studies, the researchers found that only 46 (58%) of the studies utilised HM as a construct, while 33 studies (42%) omitted the construct.…”
Section: Literature Review Utaut2mentioning
confidence: 56%
See 2 more Smart Citations
“…In information system research, HM has been found to influence technology acceptance and use (Childers et al, 2001;Thong et al, 2006;Van der Heijden, 2004). From the literature, HM is generally a predictor of BI, a finding that is aligned with what was proposed by Venkatesh et al ( 2012) (Ashraf et al, 2023;Avci & Acvi, 2022, Azizi et al, 2020Bervell et al, 2021;de Moraes & Cabello, 2017;Fathima Sanjeetha & Sabraz Nawaz, 2020;Hu et al, 2020, Kalinkara & Talan, 2022Kumar & Bervell, 2019;Moorthy et al, 2019b;Nikolopoulou et al, 2020;Raman & Don, 2013;Zhou et al, 2022). However, when Tamilmani et al (2019) conducted a meta-analysis of 79 UTAUT2 studies, the researchers found that only 46 (58%) of the studies utilised HM as a construct, while 33 studies (42%) omitted the construct.…”
Section: Literature Review Utaut2mentioning
confidence: 56%
“…However, in the UTAUT2 model, FC is posited to predict both BI and UB (Venkatesh et al, 2012). FC remained a predictor of BI in many later UTAUT2 studies (Arain et al, 2018;Azizi et al, 2020;Bhimasta & Suprapto, 2016;El-Masri & Tarhini, 2017;Faqih & Jaradat, 2021;Farooq et al, 2017;Fathima Sanjeetha & Sabraz Nawaz, 2020;Gengfu & Chotiyaputta, 2019;Gunawan et al, 2019;Hu et al, 2020;Kalinkara & Talan, 2022;Meet et al, 2022;Mishra et al, 2022;Raman & Don, 2013;Rudhumbu, 2022;Tseng et al, 2019;Widjaja et al, 2020;Zacharis & Nikolopoulou, 2022). The discussion on FC as a predictor of UB is sometimes not straightforward as in many studies.…”
Section: Literature Review Utaut2mentioning
confidence: 99%
See 1 more Smart Citation
“…Kalinkara & Talan's [21] study examined the students' intentions and behaviors regarding the UBYS system-a learning management system-through the lens of the UTAUT-2 paradigm. The structural equation model was also utilized in the research.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Tarik Talan, Yunus Doğan, Yusuf Kalinkara facilitating situation, hedonistic motivation, price and habit, which are the components of the model, affect behavioral intention (Ahmed, & Kabir, 2018). Online learning, which has come to the fore due to the pandemic, is carried out with various tools (Kalinkara, & Talan, 2022). One of the tools used in online learning through internet-based learning management systems is Google Classroom.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%